2018
DOI: 10.1016/j.cellimm.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of checkpoint inhibition in the treatment of multiple myeloma

Abstract: Despite significant improvements in the overall survival of patients with multiple myeloma (MM) over the past 15 years, the disease remains incurable. Treatment options are limited for patients who have relapsed or are refractory to immunomodulatory drugs (IMiDs), proteasome inhibitors, and monoclonal antibodies. In these patients, immunotherapies such as checkpoint inhibitors, oncolytic vaccines, and chimeric antigen receptor (CAR) T cells provide a potentially effective alternative treatment. While checkpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 172 publications
0
12
0
Order By: Relevance
“…Although the development of immune checkpoint inhibitors and advances in nextgeneration sequencing technology have revealed the existence of neoantigens derived from somatic mutations in cancer cells, several types of cancers, including leukaemia, have only a small number of neoantigens, due to rare somatic mutations [15,16]. Multiple myeloma is known to be resistant to ICIs [17], suggesting that there are few neoantigens in this haematological malignancy. Therefore, shared cancer antigens highly expressed in myeloma cells are promising targets in immunotherapies for this disease, including vaccination using cancer-specific peptides [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although the development of immune checkpoint inhibitors and advances in nextgeneration sequencing technology have revealed the existence of neoantigens derived from somatic mutations in cancer cells, several types of cancers, including leukaemia, have only a small number of neoantigens, due to rare somatic mutations [15,16]. Multiple myeloma is known to be resistant to ICIs [17], suggesting that there are few neoantigens in this haematological malignancy. Therefore, shared cancer antigens highly expressed in myeloma cells are promising targets in immunotherapies for this disease, including vaccination using cancer-specific peptides [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, on KEYNOTE-013 study, Ribrag and colleagues assessed the clinical efficacy of the anti-PD-1 mAb pembrolizumab as single agent in patients with RRMM. No patient of the 30 enrolled in the study experienced any response and the best outcome observed was again disease stabilization (Paul et al, 2018).…”
Section: Immunotherapy In MMmentioning
confidence: 99%
“…The receptors NKG2D and DNAM-1 are required for NK cell-mediated killing by identifying ligands RAE-1 and PVR expressed on MM cells, respectively ( 74 , 75 ). However, the expression of these receptors decreases on NK cells derived from MM patients, resulting in impairment of NK cell function ( 76 , 77 ). Several studies have suggested that hypoxia decreases NKG2D expression on NK cell surface, partially by hypoxic-tumor-derived micro-vesicles expressing immune modulatory factor TGF-β ( 78 , 79 ).…”
Section: The Impact Of Cellular Metabolic Changes On the Tme And Immumentioning
confidence: 99%